New copolymers with heterocyclic pendant groups obtained from PVC using microwave-assisted process - Lamanna, Melisa Elsa (2011)
We report the synthesis of new copolymers from poly(vinyl chloride) (PVC) with 1,2,4-triazol-5-yl-sulfanyl pendant groups (PVCT) by nucleophilic substitution using microwave energetic sources. By comparing the synthesis of PVCT between microwave and thermal conditions, it was found that the use of microwave-assisted process led to higher conversion levels than that of the thermal synthesis. Moreover, significant decrease in reaction times was obtained for the microwave assisted synthesis, which avoided secondary reactions. Conversion yields were calculated from elemental analysis and the molecular weighs were analyzed by means of SEC. The molecular structures of the new copolymers were confirmed by FTIR, 13C NMR and 1H NMR spectroscopies. The morphology of the new copolymers was analyzed by SEM. Thermal properties were studied by TGA and DSC techniques.